Masters of illusion : American leadership in the media age - Rosefielde, Steven (Cambridge University Press, 2007)
Assesses the forces that will buffet the United States and the global order through 2050.
Keywords: USA -- Government; Government information -- United States.; Political culture -- United States.; National security -- United States.; United States -- Politics and government.; Information sur l'État -- États-Unis.; Culture politique -- États-Unis.; Sécurité nationale -- États-Unis.; États-Unis -- Politique et gouvernement.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Government information; National security; Political culture; Politics and government; United States; Innere Sicherheit; Politische Führung; Politische Kultur; Electronic books.